PERLINDUNGAN HUKUM KONSUMEN MELALUI JAMINAN PRODUK HALAL - Misbahul Huda (The Juris, 2020)
Regarding the halalness of non-packaged food products, Law Number 8 of 1999 concerning Consumer Protection only stipulates that business actors are prohibited from producing and/or trading goods and/or services that do not comply with the provisions for halal production, as stated in the "halal" statement contained in label. Regarding the necessity for halal information in non-packaged food products, it can be seen in Law Number 33 of 2014 concerning Halal Product Guarantee, which includes "products" in the Halal Product Law are goods and/or services related to food, beverages, drugs, cosmetics, chemical products, biological products, genetically engineered products, as well as goods used, used, or utilized by the public. Meanwhile, what is meant by halal products are products that have been declared halal in accordance with Islamic law. The Law on Halal Products clearly stipulates that products that enter, circulate, and are traded in the territory of Indonesia must be certified halal. So basically, if the product being sold is halal, then it must be certified halal. Consumer protection law is currently getting enough attention because it involves rules for the welfare of the community, not only the community as consumers who get protection, but business actors also have the same right to get protection, each has rights and obligations. The government plays a role in regulating, supervising, and controlling so as to create a conducive system that is interrelated with one another, thereby achieving the general welfare of the community. In a healthy business activity, there is a balance of legal protection between consumers and producers. The absence of balanced protection causes consumers to be in a weak position, especially if the products produced by producers are of limited product types, this of course will harm consumers. Haram foods have been described in detail in the Qur'an, while halal foods are not explained, that's why in Indonesia halal certification is regulated with the aim that consumer interests can be protected. Implementation of Halal Certification.